Варианты психологической дезадаптации у пациентов с диссоциативными расстройствами = Variants of the psychological disadaptation in patients with dissociative disorders - A. N. Stolyarenko (Kazimierz Wielki University, 2016)
Stolyarenko A. N. Варианты психологической дезадаптации у пациентов с диссоциативными расстройствами = Variants of the psychological disadaptation in patients with dissociative disorders. Journal of Education, Health and Sport. 2016;6(4):11-20. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.49157 http://ojs.ukw.edu.pl/index.php/johs/article/view/3442     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.03.2016. Revised 20.03.2016. Accepted: 05.04.2016.   Варианты психологической дезадаптации у пациентов с диссоциативными расстройствами   А.Н.Столяренко   Запорожский государственный медицинский университет МЗ Украины, Запорожье, Украина   Реферат В рамках диссоциативных расстройств, эффективность терапевтической тактики определяется не столько адекватной психофармакотерапией, сколько конгруэнтностью психотерапевтических вмешательств состоянию пациента. В этом контексте важное значение приобретает верный выбор психотерапевтических методик, направленных на нивелирование как дискомплаентных личностно-психологические особенности пациента, так и дезадаптационных моделей реагирования на психотравмирующую ситуацию. Цель исследования - установить и изучить варианты психологической дезадаптации в контексте диссоциативных расстройств и проследить их взаимосвязь с преморбидными личностно-психологическими особенностями пациентов. На базе КУ «Областная клиническая психиатрическая больница» ЗОР были обследованы 108 пациентов с диссоциативными расстройствами. Методы исследования: анамнестический, катамнестический, клинико-психопатологический, психодиагностический. В результате исследования установлены основной и аранжирующие варианты психологической дезадаптации у пациентов с диссоциативными расстройствами. Доминирующими аранжирующими вариантами психологической дезадаптации среди пациентов с диссоциативными расстройствами, выступали тревожный (16 чел. - 14,81%), истероидный и неврастенический (по 14 чел. - 12,96%), фобический и гипотимный (по 12 чел. - 11,11%), и психосоматический (11 чел. - 10,19%). Установленные варианты психологической дезадаптации у пациентов с диссоциативными расстройствами призваны помочь в выборе конгруэнтных методов и методик терапии для улучшения комплаенса больных к терапии.   Ключевые слова: диссоциацивное расстройство, черты личности, психодиагностика.             Variants of the PSYCHOLOGICAL DISADAPTATION IN PATIENTS WITH DISSOCIATIVE DISORDERS   A. N. Stolyarenko   Zaporizhzhia State medical University Ministry of Healthcare of Ukraine, Zaporizhzhia, Ukraine   Summary Within the dissociative disorders, effectiveness of treatment is determined not so much by adequate psychopharmacotherapy, many congruence psychotherapeutic interventions to the patient's condition. In this context, it is important the right choice of psychotherapeutic techniques aimed at leveling as discomplete personal and psychological characteristics of the patient, and maladaptive patterns of responding to stressful situation. The purpose of the study is to establish and to explore options for psychological maladjustment in the context of dissociative disorders and to trace their relationship to premorbid personality and psychological characteristics of patients. On the basis of Public Health Institution «Regional clinical mental hospital» of the Zaporizhzhian regional council examined 108 patients with dissociative disorders. Research methods: anamnestic, follow-up, clinical-psychopathological, psychodiagnostic. The study set basic and framing variants psychological disadaptation in patients with dissociative disorders. The dominant framing variants psychological maladjustment among patients with dissociative disorders were alarming (16 people - 14,81%), hysterical and neurasthenic (14 people - 12,96%), phobic and hypotony (12 person - to 11.11%) and psychosomatic (11 people - 10,19%)variants. Installed options psychological disadaptation in patients with dissociative disorders are designed to assist in the selection of congruent methods and techniques of therapy to improve compliance of patients to therapy.   Key words: dissociative disorders, personality features, disadaptation, psychodiagnostics.